The bilingual school in the United States : a documentary history - Ramsey, Paul J. (Research in bilingual education., 2012)
This much-needed volume is an edited collection of primary sources that document the history of bilingual education in U.S. public schools during the nineteenth and twentieth centuries. Part I of the volume examines the development of dual-language programs for immigrants, colonized Mexicans, and Native Americans during the nineteenth century. Part II considers the attacks on bilingual education during the Progressive-era drive for an English-only curriculum and during the First World War. Part III explores the resurgence of bilingual activities, particularly among Spanish speakers and Native Americans, during the interwar period and details the rise of the federal government's involvement in bilingual instruction during the post-WWII decades. Part IV of the volume examines the recent campaigns against bilingual education and explores dual-language practices in today's classrooms. A compilation of school reports, letters, government documents, and other primary sources, this volume provides rich insights into the history of this very contentious educational policy and practice and will be of great interest to historians and language scholars, as well as to educational practitioners and policymakers.